PENINGKATKAN KETERAMPILAN COLLABORATIVE DAN HASIL BELAJAR SISWA KELAS 4 MELALUI MODEL PEMBELAJARAN TWO STAY TWO STRAY - Samarinda Paembonan; Mawardi Mawardi; Suhandi Astuti (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2019)
ABSTRACTOne of the problems faced in thematic learning in SDN Sidorejo Lor 05 Salatigais the lack of collaborative skills of students so that this will have an impact on studentlearning outcomes that are also low. Based on these problems, this study aims to improvecollaborative skills and student learning outcomes through the Two Stay Two Straylearning model. The type used in this study is Class Action Research (CAR). While thedata collection instruments include observation sheets, test questions, andquestionnaires. The data analysis technique uses descriptive comparative techniques.The subjects in this study were 4th grade students of SDN Sidorejo Lor 05 Salatiga with32 students consisting of 13 male students and 19 female students. The results of thisstudy indicate an increase in collaborative skills and student learning outcomes, this isevidenced by the average value of collaborative skills of students in the first cycle of56.94% and increased again in the second cycle of 68.94, while for student learningoutcomes in the first cycle shows the average value the student score is 74, after thesecond cycle student learning outcomes increase with an average value of 80. Thus theresults show that by applying the Two Stay Two Stray learning model in the learningprocess can improve collaborative skills and student learning outcomes.Keywords: Collaborative Skills, Learning Outcomes, Two Stay Two Stray